INTERPRETATION OF THE IMAGE OF THE MOTHER IN OTKIR KASHIMOV’S STORY “THE WORKS OF THE WORLD” AND NOVEL “BETWEEN TWO DOORS” - Kalandarova Dilafruz Abdujamilovna; Isokjonova Muslimaxon Ikromjon kizi (Innovate Conferences, 2025)
This article focuses on the image of Rana in Otkir Hoshimov’s novel “Between Two Doors”, the image of Aunt Umri in the story “The Works of the World”, and the image of a mother in the story “Carpet Socks”. In the above-mentioned works of the writer, the image of women who sometimes deserve the image of a mother, and sometimes who have tarnished this title, is subjected to comparative analysis.
Keywords: writer, novel, short story, narrative, image, image of mother, analysis, interpretation, comparative analysis.